Apps on Prescription in the Medical Office, but how? A Case-based Problem Outline of Medical-ethical Implications of DHA Usage Apps auf Rezept in der Arztpraxis, aber wie? Fallbasierter Problemaufriss medizinethischer Implikationen bei der Nutzung von DiGA - Kuhn, Eva; Rogge, Annette; Schreyer, Korbinian Felix; Buyx, Alena (Gesundheitswesen, 2022)
Background Since the approval of the digital care law (Digitale-Versorgung-Gesetz-DVG) on 19.12.2019, physicians have been able to prescribe digital health applications (DHA). Patients are now entitled to such applications. The present article sets out to clarify how physicians should integrate DHAs into patient care and the ethical responsibilities they have in this process. Methods Based on an adapted principle-oriented case analysis, three hypothetical case scenarios are discussed. The argumentative-analytical approach is based on four established principles of medical ethics (following Beauchamp and Childress), namely autonomy, beneficence, non-maleficence and justice, as well as on the Model Professional Code of Conduct for Physicians working in Germany (MBO-A). Results When prescribing DHAs, physicians need to give patients additional information on the specific risks that result from such applications. Special attention must be paid to patients' digital health literacy. Furthermore, DHAs should not replace personal contact, but complement and support guideline-based treatment. To enable patients to use DHAs more independently, we recommend an 'app anamnesis'. Conclusion Beauchamp's and Childress's principles as well as the MBO-A are instructive for handling DHAs in patient care. The Dos and Don'ts presented must be complemented by further guidance providing orientation for physicians on how to integrate DHAs in patient care in a responsible way.
CRIS-Team Scopus Importer:2023-03-08
Keywords: digital health literacy; informed consent; medical app; mHealth; principlism